check the picture below.
[tex]\bf ~~~~~~\textit{initial velocity}\\\\
\begin{array}{llll}
~~~~~~\textit{in feet}\\\\
h(t) = -16t^2+v_ot+h_o \\\\
\end{array}
\quad
\begin{cases}
v_o=\stackrel{\textit{initial velocity of the object}}{120}\\\\
h_o=\stackrel{\textit{initial height of the object}}{2}\\\\
h=\stackrel{}{\textit{height of the object at "t" seconds}}
\end{cases}
\\\\\\
h(t)=-16t^2+120t+2[/tex]
[tex]\bf \textit{ vertex of a vertical parabola, using coefficients}\\\\
\begin{array}{llll}
h(t)= &{{ -16}}t^2&{{ +120}}t&{{ +2}}\\
&\uparrow &\uparrow &\uparrow \\
&a&b&c
\end{array}\qquad
\left(-\cfrac{{{ b}}}{2{{ a}}}\quad ,\quad {{ c}}-\cfrac{{{ b}}^2}{4{{ a}}}\right)
\\\\\\
\left(-\cfrac{120}{2(-16)}~~,~~2-\cfrac{120^2}{4(-16)} \right)\implies \left( \cfrac{15}{4}~~,~~2+\cfrac{14400}{32} \right)[/tex]
[tex]\bf \left( \cfrac{15}{4}~~,~~2+450 \right)\implies \left( \stackrel{seconds}{3\frac{3}{4}}~~,~~\stackrel{feet}{452} \right)[/tex]